Design of Automatic Coffee Bean Roaster Based on Arduino Uno Microcontroller - Romi Agustian; Andik Bintoro; Rosdiana Rosdiana; Misbahul Jannah; Salahuddin Salahuddin; Waleed Khalid Ahmed Al-Ani (Indonesian Scientific Journal, 2022)
This study aims to design an automatic coffee bean roaster machine to meet the needs of supporting tools and machines for the downstream coffee industry. Design of a coffee bean roaster based on an Arduino uno microcontroller. The design is carried out by designing an automatic coffee bean roaster which includes making a tool framework, making programs or commands on the Arduino Uno, testing the automatic coffee bean design tool based on the Arduino Uno microcontroller. The results of the design of the automatic coffee bean roasting machine based on the Arduino uno microcontroller are functioning well. The automatic coffee bean roaster machine based on the Arduino Uno microcontroller consists of a 24V DC Power supply, Ds18b20 Sensor, 12V DC Fan, L298N Motor Driver, Servo, 12V DC Motor, 16x2 LCD, Arduino Atmega2560 Microcontroller, coffee bean roasting container and frame. Functional test results show that all components of the roasting machine are able to function according to their functions. By controlling the control system on the heating element based on a temperature of 1000C which is read by the Ds18b20 temperature sensor using the Arduino Uno program, which is driven by a servo motor with an automatic coffee roaster capacity of 250 grams per one roast.